Penanaman Nilai Parenting Berbasis Islamiyah Pada Anggota Majelis Ta'lim Ar-Raudhah Sebagai Upaya Mencegah Kenakalan Anak di Mesjid Ar-Raudhah, Kelurahan Air Dingin, Kota Pekanbaru - Neri Widya Ramailis; Ema Fitri Lubis; Rio Sundari; Widya Eka Putri; Gitya Kusuma Prianty; Rosmayani Rosmayani (PELANTAR PRESS, 2026)
Juvenile delinquency is a complex social issue that requires preventive efforts through strengthening the role of the family, particularly in parenting practices. Islamic-based parenting integrates religious values with moral, social, and emotional development, making it a relevant approach to addressing children’s behavioral problems. This community service program aimed to improve parents’ understanding and skills in implementing Islamic parenting values among members of the Ar-Raudhah Majelis Ta’lim at Ar-Raudhah Mosque, Pekanbaru. The program employed a participatory counseling approach based on situation analysis and needs assessment. Activities were conducted through socialization sessions, interactive lectures, group discussions, and parenting simulations. Evaluation was carried out through participant feedback and reflection to assess changes in understanding and attitudes. The results indicate an increase in participants’ awareness and comprehension of Islamic parenting principles, particularly regarding role modeling, effective communication, and balanced supervision in child development. The program also strengthened collective awareness within the community about the importance of collaborative efforts in preventing juvenile delinquency. These findings suggest that community-based parenting education grounded in religious values can effectively strengthen parents’ capacity and reinforce the family’s role as the primary institution in preventing juvenile delinquency